Nickel Availability and hupSL Activation by Heterologous Regulators Limit Symbiotic Expression of the Rhizobium leguminosarum bv. Viciae Hydrogenase System in Hup(−) Rhizobia - Brito, Belén (American Society for Microbiology, 2000)
A limited number of Rhizobium and Bradyrhizobium strains possess a hydrogen uptake (Hup) system that recycles the hydrogen released from the nitrogen fixation process in legume nodules. To extend this ability to rhizobia that nodulate agronomically important crops, we investigated factors that affect the expression of a cosmid-borne Hup system from Rhizobium leguminosarum bv. viciae UPM791 in R. leguminosarum bv. viciae, Rhizobium etli, Mesorhizobium loti, and Sinorhizobium meliloti Hup(−) strains. After cosmid pAL618 carrying the entire hup system of strain UPM791 was introduced, all recipient strains acquired the ability to oxidize H(2) in symbioses with their hosts, although the levels of hydrogenase activity were found to be strain and species dependent. The levels of hydrogenase activity were correlated with the levels of nickel-dependent processing of the hydrogenase structural polypeptides and with transcription of structural genes. Expression of the NifA-dependent hupSL promoter varied depending on the genetic background, while the hyp operon, which is controlled by the FnrN transcriptional regulator, was expressed at similar levels in all recipient strains. With the exception of the R. etli-bean symbiosis, the availability of nickel to bacteroids strongly affected hydrogenase processing and activity in the systems tested. Our results indicate that efficient transcriptional activation by heterologous regulators and processing of the hydrogenase as a function of the availability of nickel to the bacteroid are relevant factors that affect hydrogenase expression in heterologous rhizobia.